Purulent lymphadenitis caused by Staphylococcus argenteus, representing the first Japanese case of Staphylococcus argenteus (multilocus sequence type 2250) infection in a 12-year-old boy. Issue 11 (November 2018) - Ohnishi, Takuma; Shinjoh, Masayoshi; Ohara, Hirotoshi; Kawai, Toshinao; Kamimaki, Isamu; Mizushima, Ryo; Kamada, Keisuke; Itakura, Yasutomo; Iguchi, Shigekazu; Uzawa, Yutaka; Yoshida, Atsushi; Kikuchi, Ken
Abstract: Staphylococcus argenteus is a novel species separated from a strain of coagulase-positive, non-pigmented S. aureus . Although S. argenteus has been reported to occur globally, multilocus sequence type (ST) 2250 is mainly found in Northeastern Thailand. Because conventional biochemical testing misidentifies this pathogen as S. aureus, multilocus sequence typing (MLST) or nucA sequencing is recommended to distinguish between S. argenteus and S. auereus . The patient was a previously healthy 12-year-old boy who was admitted because of right inguinal lymphadenitis and cellulitis. Although intravenous cefazolin was administered, his lymphadenitis worsened and formed an abscess on day 6 of hospitalization. Incision and drainage were performed on day 7 of hospitalization. Cefazolin was changed to oral cefaclor, and the patient was successfully treated over a period of 5 weeks. No recurrence was observed throughout 12-months of follow-up. He had a history of right axillary lymph node abscess 2 months before this admission, which was successfully treated with incision, drainage, and antibiotic therapy. He has lived in Japan since birth and never traveled abroad. He had no opportunity to interact with foreigners. His immune function, especially neutrophil function, was tested and we did not find any dysfunction. First, methicillin-sensitive S. aureus was misidentified from the abscess culture. Subsequently, the causative agent was re-identified as S. argenteus ST2250 based on MLST. To our knowledge, this is the first case of S. argenteus ST2250 infection in Japan. This pathogen should be taken into consideration in the diagnosis if the patient has atypical non-pigmented S. aureus .